Forming an alumni association relief group to address the needs of Indigenous peoples in Tripura, India during the COVID-19 pandemic. Issue 1 (2nd January 2022) - Tripura, Biswaranjan
ABSTRACT: In this narrative essay, I reflect on the steps taken and challenges encountered in forming and meeting the goals of an alumni group aimed at supporting vulnerable indigenous communities in Tripura, India during the COVID-19 pandemic.